2011
DOI: 10.20965/jaciii.2011.p0962
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Synchrony Judgment and its Relation to the Auditory Brainstem Response: the Difference Between Pianists and Non-Pianists

Abstract: Synchrony judgment is one of the most important abilities for musicians. Only a few milliseconds of onset asynchrony result in a significant difference in musical expression. Using behavioural responses and Auditory Brainstem Responses (ABR), this study investigates whether synchrony judgment accuracy improves with training and, if so, whether physiological responses are also changed through training. Psychoacoustic experiments showed that accuracy of synchrony judgment of pianists was higher than that of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For delay direction, the thresholds of compensated delay (C) were higher than those of enhanced delay (E). It means that the accuracy of synchrony judgment on compensated delay (C) was lower than that of enhanced delay (E) as previous study reported [3,9,7,8].…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…For delay direction, the thresholds of compensated delay (C) were higher than those of enhanced delay (E). It means that the accuracy of synchrony judgment on compensated delay (C) was lower than that of enhanced delay (E) as previous study reported [3,9,7,8].…”
Section: Resultsmentioning
confidence: 73%
“…In previous physiological studies [6,7,8], the auditory brainstem response (ABR) was observed, when participants listened to the compensated delay chirp, the enhanced delay chirp and the pulse respectively. As a result, the ABR wave-Vs that evoked by the compensated delay chirp appeared to be the most salient, and the enhanced delay chirp had the gentlest peak.…”
Section: Cochlear Delaymentioning
confidence: 99%
“…However, while explicit knowledge of highly skilled workers has been studied in a variety of special skill sets, the methods used in these studies remain subject to discussion. For example, there is a lack of consensus regarding the defined quality and whether the skills demonstrated represent the best practice [4][5][6]. The author has also studied various training methods used for producing skilled workers [7][8][9][10].…”
mentioning
confidence: 99%